1992
DOI: 10.1128/mcb.12.1.190
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the fibroblast transformation potential of GTPase-deficient gip2 oncogenes.

Abstract: Expression of GTPase-deficient Gi2 a subunit (ai2) mutant polypeptides and overexpression of the wild-type oi2 polypeptide in Rat la, Swiss 3T3, and NIH 3T3 fibroblasts altered normal growth regulation and induced a loss of contact inhibition. In Rat la cells (but not in NIH 3T3 or Swiss 3T3 cells), expression of the GTPase-deficient ai2 mutant polypeptides allowed colony formation in soft agar, which correlated with a loss in anchorage dependence and a decreased serum requirement. The altered growth regulator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
59
0
3

Year Published

1994
1994
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(68 citation statements)
references
References 44 publications
6
59
0
3
Order By: Relevance
“…However, the ®nding that the expression of gip2 constitutively activates MEK-ERK signaling in Rat1a cells indicated that this could be the major mechanism through which gip2 regulates cell growth (Gupta et al, 1992b). Interestingly it has been observed that gip2-mediated activation of MEK-ERK pathway is independent of functional Ras .…”
Section: Ga I and The Gip2 Oncogenementioning
confidence: 99%
“…However, the ®nding that the expression of gip2 constitutively activates MEK-ERK signaling in Rat1a cells indicated that this could be the major mechanism through which gip2 regulates cell growth (Gupta et al, 1992b). Interestingly it has been observed that gip2-mediated activation of MEK-ERK pathway is independent of functional Ras .…”
Section: Ga I and The Gip2 Oncogenementioning
confidence: 99%
“…Studies focused on defining the molecular basis for such mitogenic activity identified the role of Ga i in the regulation of the ERK module (L'Allemain et al, 1991;Pouyssegur and Seuwen, 1992b). Expression of the GTPase deficient, constitutively activated mutant of Ga i2 resulted in the oncogenic transformation of Rat1 fibroblasts Gupta et al, 1992b). Functional characterization of the transformed phenotype indicated that expression of the activated Ga i2 was associated with constitutive activation of p44-ERK activity (Gupta et al, 1992a).…”
Section: Regulation Of Mapks By G Imentioning
confidence: 99%
“…The gip2 oncogene, which was identi®ed in both human adrenal cortical tumors and ovarian sex cord stromal tumors, encodes a constitutively activating mutation in the Ga i subunit (Lyons et al, 1990). gip2 is fully transforming when overexpressed in Rat-1 ®broblasts (Gupta et al, 1992;Pace et al, 1991). The wild type Ga 12 subunit (gep oncogene) was isolated in a screen of a soft tissue sarcoma library for proteins whose expression cause focus formation in NIH3T3 cells (Chan et al, 1993).…”
Section: Oncogenic Potential Of Gpcrs and Heterotrimeric G Proteinsmentioning
confidence: 99%